2022
DOI: 10.3389/fnut.2021.825495
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Malic Acid Supplementation Induces Skeletal Muscle Fiber-Type Transition of Weaned Piglets and Further Improves Meat Quality of Finishing Pigs

Abstract: The aim of this study was to investigate effects of dietary malic acid supplementation on skeletal muscle fiber-type transition during nursery period and the subsequent meat quality of finishing pigs. Results showed that malic acid supplementation for 28 days increased oxidative fiber percentage of weaned piglets, accompanied by the increased aerobic oxidation in serum and longissimus thoracis (LT) muscle. Additionally, activities of total antioxidant capacity and glutathione peroxidase in serum were increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
5
13
0
Order By: Relevance
“…In addition, approximately 100 g of each meat sample was weighed, sealed in a plastic bag and heated in a constant temperature water bath with 75 °C water for 30 min in one cooking batch, and then residual moisture was removed from the meat sample, and the latter was cooled to room temperature and reweighed to calculate cooking loss. Shear force was determined as described in our previous study using a digital-display muscle tenderness meter (C-LM3B, Tenovo, Harbin, China) with a speed of 300 mm/min [ 33 ]. The mean value for 10 subsamples of each sample was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, approximately 100 g of each meat sample was weighed, sealed in a plastic bag and heated in a constant temperature water bath with 75 °C water for 30 min in one cooking batch, and then residual moisture was removed from the meat sample, and the latter was cooled to room temperature and reweighed to calculate cooking loss. Shear force was determined as described in our previous study using a digital-display muscle tenderness meter (C-LM3B, Tenovo, Harbin, China) with a speed of 300 mm/min [ 33 ]. The mean value for 10 subsamples of each sample was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The initial and final weight was recorded, and cooking loss was determined by calculating weight change percentage. Then, the dried muscle sample was ground into powder and analyzed for intramuscular (IMF) fat content, as previously described [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…They were then cooled to room temperature, and samples were trimmed to uniform cubes of about 1 cm 3 . Texture indexes including shear force, hardness, adhesiveness, cohesiveness, springiness, gumminess and chewiness were measured using a Texture Analyzer (TMS-Touch, Food Technology Corp., Sterling, VA, USA), as described previously [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meat with a high content of type I myofibers has higher water retention and tenderness and a brighter red color, and vice versa for meat with type II myofibers. It was reported that myofiber types could be converted as follows: I ↔ IIa ↔ IIx ↔ IIb, which were affected by breed, feeding model, sex, age and nutrition (9)(10)(11)(12)(13). Therefore, adjusting myofiber type transformation is an important way to improve meat quality.…”
Section: Introductionmentioning
confidence: 99%